2013
DOI: 10.3109/17435390.2013.855831
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of toxic action of Ag, ZnO and CuO nanoparticles to selected ecotoxicological test organisms and mammalian cells in vitro: A comparative review

Abstract: Silver, ZnO and CuO nanoparticles (NPs) are increasingly used as biocides. There is however increasing evidence of their threat to ''non-target'' organisms. In such a context, the understanding of the toxicity mechanisms is crucial for both the design of more efficient nanoantimicrobials, i.e. for ''toxic by design'' and at the same time for the design of nanomaterials that are biologically and/or environmentally benign throughout their life-cycle (safe by design). This review provides a comprehensive and crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
190
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(202 citation statements)
references
References 143 publications
(216 reference statements)
7
190
0
5
Order By: Relevance
“…Unlike earlier studies (15,27,28), which used whole lymphocyte populations, ours is a novel approach that compares the effects of ZnO NPs by combining DPASV and HR-ICPMS with two comet assays.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike earlier studies (15,27,28), which used whole lymphocyte populations, ours is a novel approach that compares the effects of ZnO NPs by combining DPASV and HR-ICPMS with two comet assays.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several reviews have highlighted oxidative stress arising from the generation of ROS as the primary mode of action of ENPs towards aquatic organisms when effects cannot be related to the dissolution or physical interactions of ENPs 14, 135, 136. However, the link between particle properties and ROS generation is still undetermined in ecotoxicology;96, 134 even whether size is actually correlated to toxicity is at times noted as being controversial,134 and von Moss and Slaveykova96 describe the relationship between particle properties and ROS generation as “ the most controversial issue and greatest challenge to nano(eco)toxicology ”.…”
Section: Known Mechanisms Of Enp Ecotoxicity—the Question Of Particlmentioning
confidence: 99%
“…Therefore, the calculated log T e ion value indicated that the detected toxicities were not derived from Ag + . Toxicological investigations of NPs have suggested that the physicochemical properties of NPs, e.g., shape, size, surface charge, solubility, chemical composition, binding ability to biological sites (proteins and peptides), and their metabolic breakdown, influence the toxicity of NPs (Bondarenko et al 2013;Golbamaki et al 2015;He et al 2015;Ivask et al 2014b;McCracken et al 2016;Pettibone and Louie 2015;von Moos et al 2014). Based on these factors and available toxicological data, the following trends were observed.…”
Section: +mentioning
confidence: 99%